On Linear Difference Equations for Which the Global Periodicity Implies the Existence of an Equilibrium - István Győri; László Horváth (Abstract and Applied Analysis)
It is proved that any first-order globally periodic linear inhomogeneous autonomous difference equation defined by a linear operator with closed range in a Banach space has an equilibrium. This result is extended for higher order linear inhomogeneous system in a real or complex Euclidean space. The work was highly motivated by the early works of Smith (1934, 1941) and the papers of Kister (1961) and Bas (2011).